2018
DOI: 10.3892/ol.2018.8419
|View full text |Cite|
|
Sign up to set email alerts
|

The roles of RUNX3 in cervical cancer cells in�vitro

Abstract: Abstract. RUNX3 serves an important role in development of various types of human cancer. The purpose of the present study was to investigate the potential biological function of RUNX3 in cervical cancer cells. In the present study, a RUNX3 overexpressed model was constructed in Hec1 cells by PCDNA3.1-RUNX3 transfection. Western blot analysis was used to measure RUNX3 expression in cervical cancer cells. Immunofluorescence analysis was performed to examine subcellular localization of RUNX3 in cervical cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In the present study, the upregulated expression of RUNX3 consistently inhibited the proliferation and promoted the apoptosis of cervical cancer cells, particularly in the SiHa cell line. The results were similar to those of a recent study on cervical cancer, which reported that upregulated expression of RUNX3 inhibited the proliferation, migration and invasion of cervical cancer cells (12). According to these results, it may be concluded that RUNX3 acts as a tumor suppressor gene in cervical cancer (12).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the upregulated expression of RUNX3 consistently inhibited the proliferation and promoted the apoptosis of cervical cancer cells, particularly in the SiHa cell line. The results were similar to those of a recent study on cervical cancer, which reported that upregulated expression of RUNX3 inhibited the proliferation, migration and invasion of cervical cancer cells (12). According to these results, it may be concluded that RUNX3 acts as a tumor suppressor gene in cervical cancer (12).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, three types of cervical cancer cell lines were selected: SiHa, HeLa and C33A, infected by HPV-16, HPV-18 or not infected, respectively. It was recently reported that RUNX3 may play a key role in the development and progression of cervical cancer (12). It was also observed in the present study that RUNX3 may inhibit cervical cancer cell proliferation, particularly in the SiHa cell lines, indicating its potential function as a tumor suppressor; inconsistencies in these results may be due to the different cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…runX3 is mapped on human chromosome 1p36, and has been reported to serve as an anti-tumor gene in lung (31), bladder (32) and gastric cancer (33). li et al (21) revealed that knockdown of runX3 promoted the proliferation, migration and invasiveness of cc cells. Similarly, Gao et al (34) reported that upregulation of runX3 inhibited the proliferation of cc cells.…”
Section: Discussionmentioning
confidence: 99%
“…runX3 may also have a major role in the cellular processes of tumorigenesis and metastasis, including epithelial-mesenchymal transition (eMT) (17), adhesion (18), invasion (19) and apoptosis (20). Zhen et al (21) revealed that overexpression of runX3 suppressed the proliferation, migration and invasion of cc cells, thus suggesting that runX3 may function as a tumor suppressor in cc. However, the regulatory relationship between mir-130a-3p and runX3 in cc remains unclear.…”
Section: Introductionmentioning
confidence: 99%